Factors of Unfulfilled Rights of Wife and Children as Consequences of Divorce in Religious Court Decisions - Saleh, Taufiq; Hayatuddin, Khalisah; Wardhana, Arif Wisnu (Nurani, 2023)
PERMA Number 3 of 2017 serves as a guideline for judges in adjudicating cases involving women and can be used as a legal basis for providing protection to children who are victims of divorce. The problem discussed in this research is the implementation of PERMA in the Baturaja Religious Court. The aim of this study is to examine the issue of the non-fulfillment of the rights of the wife and children as a consequence of divorce in court decisions. A qualitative research approach with a field study design was chosen for this study. The research was conducted at the Baturaja Religious Court. The data used consisted of primary data and secondary data. Data analysis was divided into three parts: data reduction, data display, and conclusions. The research findings indicate that the implementation of PERMA Number 3 of 2017 regarding the rights of the wife and children as a consequence of divorce in the Baturaja Religious Court has not been fully implemented. This is due to several factors, such as the economic instability of the father, remarriage of the parents, psychological factors that prevent the former husband from meeting their children, and the ability of the mother to provide for the child's welfare.